2019
DOI: 10.1186/s13065-019-0550-6
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline characteristics of annealed AlN films by pulsed laser treatment for solidly mounted resonator applications

Abstract: AlN films were deposited on Si substrates using a reactive RF magnetron sputtering process and then the films were annealed by using different laser powers and wavelengths (355 nm, 532 nm and 1064 nm). For all three laser systems, the (002) peak intensity was obviously improved following laser irradiation. The improvement in the crystalline property was particularly obtained in the AlN film processed at 355 nm. In particular, given the use of the optimal laser power (0.025 W), the (002) peak intensity was 58.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…When AlN film was treated with a laser with a wavelength of 355 nm and a power of 0.025 W, the crystallinity of the film was significantly improved. The peak intensity of (002) was 58.7% higher than the untreated peak intensity [ 33 ]. However, high temperature and long treatment may have a negative impact [ 34 ], and the enhanced crystal quality of the films due to RTA hardly contributes to a significant improvement in k t 2 .…”
Section: Methodsmentioning
confidence: 99%
“…When AlN film was treated with a laser with a wavelength of 355 nm and a power of 0.025 W, the crystallinity of the film was significantly improved. The peak intensity of (002) was 58.7% higher than the untreated peak intensity [ 33 ]. However, high temperature and long treatment may have a negative impact [ 34 ], and the enhanced crystal quality of the films due to RTA hardly contributes to a significant improvement in k t 2 .…”
Section: Methodsmentioning
confidence: 99%
“…To date, pulsed laser annealing is the next promising candidate to further relieve the thermal budget of the laser annealing process, especially for the process at the back-end-of-line (BEOL) 2 , 6 . Previous studies showed the possibility of improving crystalline structures of aluminum nitride (AlN) 7 , 8 or zinc oxide (ZnO) nanofilms 9 when the structural voids can be minimized with better surface morphology 10 . Meanwhile, the laser annealing technique has also been applied to dopant activation of Be-implanted gallium nitride (GaN) 11 or silicon/germanium 12 .…”
Section: Introductionmentioning
confidence: 99%